Diagnostic and treatment methods for ulcerative colitis and colitis-associated cancer - Pandurangan, Ashok Kumar, 1982- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2021)
"This book provides innovative insights that describe the fundamental understanding of UC and CAC and the molecular mechanisms behind the etiology as well as modern diagnostic methods that are employed in UC and CAC. Current prevention and therapeutic strategies practiced in the pre-clinical level are also discussed"--